COVID-19 frontline primary health care professionals' perspectives on health system preparedness and response to the pandemic in the Mahalapye Health District, Botswana - Stephane T. Tshitenge; Justus M. Nthitu (AOSIS, 2022)
Background: The World Health Organization issued interim guidelines on essential health system preparedness and response measures for the coronavirus disease 2019 (COVID-19) pandemic. The control of the pandemic requires healthcare system preparedness and response. Aim: This study aimed to evaluate frontline COVID-19 primary health care professionals' (PHC-Ps) views on health system preparedness and response to the pandemic in the Mahalapye Health District (MHD). Setting: In March 2020, the Botswana Ministry of Health directed health districts to educate their health professionals about COVID-19. One hundred and seventy frontline PHC-Ps were trained in MHD; they evaluated the health system's preparedness and response. Methods: This was a cross-sectional study that involved a self-administered questionnaire using the Integrated Disease Surveillance and Health System response guidelines. Results: The majority (72.5%) of participants felt unprepared to deal with the COVID-19 pandemic at their level. Most of the participants (70.7%) acknowledged that the health system response plan has been followed. About half of the participants attributed a low score regarding the health system's preparedness (44.4%), its response (50.0%), and its overall performance (55.6%) to the COVID-19 pandemic. There was an association between participants' age and work experience and their overall perceptions of preparedness and response (p = 0.009 and p = 0.005, respectively). Conclusion: More than half of the participants gave a low score to the MHD regarding the health system's preparedness and response to the COVID-19 pandemic. Further studies are required to determine the causes of such attitudes and to be better prepared to respond effectively.